Remote Interoperability Testing Client for Wireless Personal Area Network Protocol - Xinyu Zhang; Xiaohong Huang; Pei Zhang (Dianxin kexue)
When the entities in one interoperability testing case were not suitable to be placed in the same physical location,the remote testing method was needed to complete the testing.In order to guarantee the success of the remote testing,a platform based on the Internet environment was built.A system structure was designed for assure the platform was suitable for wireless personal area network protocol.The framework mainly contained the device connection module and the data forwarding module.To illustrate the application of proposed approach,a real case study was proposed:the 6LoWPANs protocol.The results of the experimentation performed on this protocol were also presented.